Living Qur’an and Contemporary Moral Crises: Actualizing the Qur’anic Values of Zuhud among Indonesian Muslims - Arya Dekhan (International Journal of Islamic Studies, 2026)
This study examines the actualization of the Qur’anic values of zuhud through the living Qur’an approach as a response to the contemporary moral crises experienced by Indonesian Muslims. The study is motivated by the growing phenomena of consumerism, flexing culture, and digital materialism, which have gradually weakened the internalization of Qur’anic values in everyday life. Employing a qualitative library research design, this study integrates thematic (mauḍū‘ī) Qur’anic exegesis on verses related to zuhud with the living Qur’an framework as its analytical perspective. Primary data were obtained from the Qur’an and classical as well as contemporary exegetical works, while secondary data were drawn from scholarly literature on the Living Qur’an, zuhud, and contemporary social phenomena among Muslim communities. The findings reveal that zuhud should not be understood as poverty or the rejection of worldly life; rather, it represents a balanced ethical orientation manifested through three interconnected dimensions of spiritual (inner) zuhud, behavioral (outer) zuhud, and social zuhud. These dimensions provide practical guidance for responding to consumerist culture, fostering responsible digital behavior, and strengthening Muslim moral character. This study contributes to the development of living Qur’an scholarship by extending its focus beyond ritual practices toward the actualization of Qur’anic ethical values that remain highly relevant to the challenges faced by contemporary Muslim society.